Modern trends in nutrition for different age groups - Durava, Arina (Національний технічний університет "Харківський політехнічний інститут", 2024)
The research devoted to exploring the dietary trends of 2024, including the rise of plant-based diets, the significance of protein-rich foods, and the resurgence of flexible eating patterns like the Mediterranean diet.
Keywords: nutrition; dietary trends; plant-based diets; mediterranean diet; здоров'я людей; харчування; дієтичні тенденції; рослинні дієти